2019
DOI: 10.1111/dech.12514
|View full text |Cite
|
Sign up to set email alerts
|

Taming Foreign Exchange Derivatives Markets? Speculative Finance and Class Relations in Brazil

Abstract: This article provides a critical interrogation of the Brazilian tax on foreign exchange derivatives deployed between 2011 and 2013. It analyses the drivers of the policy-making process that led to implementation of the measure, locates it within the broader policy response regarding the management of cross-border capital flows and speculative finance, and assesses its political economy significance in light of class dynamics. The author makes three arguments. First, this innovative policy tool must be interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 53 publications
0
15
0
1
Order By: Relevance
“…While both types of perspective are insightful, a critique of political economy perspective allows uncovering aspects of uneven processes of financialization in developing economies that have been understudied or downplayed. Grounding my analysis in the critique of the state, money, and their relation, I have showed that patterns of financialization in developing economies have resulted from specific modes of managing class relations engineered by the state in order to politically contain and integrate labor (Alami 2019b). Brazil is a case in point.…”
Section: Marx's Critique Of Political Economy and Social Form-analysismentioning
confidence: 97%
See 1 more Smart Citation
“…While both types of perspective are insightful, a critique of political economy perspective allows uncovering aspects of uneven processes of financialization in developing economies that have been understudied or downplayed. Grounding my analysis in the critique of the state, money, and their relation, I have showed that patterns of financialization in developing economies have resulted from specific modes of managing class relations engineered by the state in order to politically contain and integrate labor (Alami 2019b). Brazil is a case in point.…”
Section: Marx's Critique Of Political Economy and Social Form-analysismentioning
confidence: 97%
“…However, these large financial inflows also catalysed financialization processes and accelerated the buildup of financial vulnerability. This created a number of serious challenges which ultimately contributed to the disintegration of the PT's fragile hold on power (Alami 2019b). Put differently, the specific pattern of financialization in Brazil importantly resulted from the state's attempt at containing the struggles of workers, peasants, and the poor.…”
Section: Marx's Critique Of Political Economy and Social Form-analysismentioning
confidence: 99%
“…This does not mean derivatives are not important. For example, Alami (2019) analyses the role of derivatives in foreign exchange speculation in Brazil. 3.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…A different channel through which bank flows matter is related to the exchange rate. Gross deposit flows (as well as derivative flows, see for example Alami 2019) arise in the context of foreign exchange trading. For example, the transaction examined in section 2 where the US investor sells dollar deposits to acquire Brazilian assets is likely to put upward pressure on the Brazilian real, since – everything else constant – the Brazilian bank has no excess demand for US dollars.…”
Section: Capital Flows Trade Imbalances and Geographically Uneven Fin...mentioning
confidence: 99%
“…While Treasury officials and political elites may hold to the position that maintaining a financialized, neoliberal landscape is the most efficient way to attract investment in mining as well as foreign capital into state bonds, there is evidence that this type of developmental and redistributive arrangement is unsustainable. For example, the PT (Worker's Party) in Brazil relied on foreign capital inflows to finance redistribution and investment in education for an extended period of time, yet this practice eventually led to currency appreciation and macroeconomic instability, frustrating industrial policy and even prompting policy makers to impose regulations on foreign exchange derivatives and portfolio capital inflows (Alami, 2019; Loureiro, 2020). This would suggest that if Treasury officials continue to veto policy proposals that could potentially allow South Africa to upgrade industrially and generate internal resources in a consistent fashion then the current economic regime, in light of the ongoing fiscal crisis in the country, will soon run out of steam.…”
Section: Financialized Neoliberalism and South Africa's Social Welfar...mentioning
confidence: 99%